Transformations in News Reporting Practices: An In-Depth Qualitative Study of Social Media Usage among Malaysian Newspaper Journalists - Loganathan, Kannan; Kunasekaran, Puvaneswaran; Ponnan, Ramachandran; Salman, Ali; De Rycker, Antoon (International Journal of Psychosocial Rehabilitation, 2020)
Technology continues to change ways journalists gather and deliver news. This qualitative study examines the role and influence of social media in changing the ways Malaysian journalists gather and deliver news. In-depth interviews were conducted among print media journalists in Klang Valley to determine the use and influence of social media in their work. The Diffusion of Innovation theory was used as a foundation to explore how journalists adopted social media in news gathering and reporting. The study found that social media was advantageous and indispensable in news gathering and reporting as it is resourceful and convenient. It also found that social media dictates news in print media and has induced an urgency to be first with information. Concerns were raised that inaccurate or false information could be released and that the use of social media has burdened journalists with additional roles.